PENINGKATAN PENGETAHUAN TENTANG MASA MENOPAUSE BAGI WARGA DESA SINDANGGALIH KARANGPAWITAN GARUT - andhika, Andhika Lungguh Perceka; N. Ai Erlinawati; Desy Syswianti; Hasbi Taobah Ramdani; Herlin Rusyani (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
Menopause is not a disease or disorder and occurs at the end of the last menstrual cycle but certainty is only obtained if a woman has not experienced her menstrual cycle for at least 12 months. The purpose of this community service activity is to increase mothers' understanding of menopause and problems, so that they can experience menopause. The method used was face-to-face counseling held at RW 06 Sindanggalih Village Karangpawitan Garut by distributing questionnaires before and after counseling to determine the level of knowledge and understanding of the community about menopause. Results: This community service resulted in information that the level of understanding of the community before and after counseling increased significantly from 52% to 84%. Conclusion: The counseling activities carried out are expected to make mothers understand more about menopause and overcome any problems during menopause. The material provided is knowledge about menopause and is delivered in a straightforward and clear manner. the community becomes enthusiastic in participating in counseling activities, given the great benefits that can be taken from community service activities.Keywords: Community services, Knowledge, MenopauseABST